A Community Hospital‐County Health Department Partnership to Reduce Preventable Readmissions: Lessons Learned for Population Health Management. Issue 4 (July 2015) - Kurtzman, Jordan H.
Abstract : EXECUTIVE SUMMARY: Healthcare reform has prompted hospital executives to adopt new strategies aimed at population health management. Research regarding the broad determinants of health suggests that if hospitals are to build successful population health management models, they must engage in collaborative partnerships with a variety of community stakeholders. In this report, the author describes a collaborative partnership between a community hospital and a county health department to reduce preventable readmissions. This program illustrates the important role that health information technology (HIT), managerial systems, new processes, and hospital culture play in collaborations with external parties. On a larger scale, these facilitators are key factors in developing population health business models such as accountable care organizations. A sound hospital infrastructure should be supported by hospital leaders and staff who are held accountable for community initiatives and communicate transparently with external partners.